Age and correlation of the Proterozoic Mafingi Group in Malawi. (December 2022) - Thomas, Robert J.; Fullgraf, Thomas; Charles, Nicolas; le Bayon, Benjamin; Boger, Steven D.; Frei, Dirk; Lach, Philippe; Dombola, Kondwani
Abstract: The low-grade Mafingi Group form a restricted sequence of Proterozoic arenaceous and pelitic metasedimentary rocks which locally lie unconformably on the Palaeoproterozoic Ubendian Domain basement gneisses in northern Malawi. Four samples were taken from different parts of the sequence, in order to obtain detrital zircons for U–Pb geochronology to constrain their maximum age of deposition, provenance and thereby to suggest correlations with other sequences in the wider SE African region. Three samples, including one from the Type Area (Mafingi Hills), and two from different tectonic slivers within the Ubendian gneisses, gave maximum deposition ages of around 1800 Ma. A third sample, also from a tectonic sliver gave a much younger maximum depositional age of ∼1500 Ma. Apart from this, all samples show similar zircon age spectra, with a major composite age-peak at ∼1900 ± 100 Ma from zircon detritus most probably derived from the local Ubendian Domain basement. Three samples show a very small Archaean age component probably derived from the Tanzania Craton which lies to the NE. The most NE sample of strongly recrystallised "Virauli Quartzite", apparently interlayered with Ubendian gneisses of the Ufipa Subdomain, contained metamorphic zircon grains dated at ∼560 Ma, reflective of a Pan-African overprint within the local western margin of the wider East African Orogen. Significantly, no evidence of ∼1 Ga (Irumide) metamorphism was detected in any of the samples. The three older samples gave maximum depositional ages confirming previous proposed correlations of the Mafingi Group with the Manshya River Group of the Muva Supergroup in Zambia. Despite having a similar detrital age spectrum to the other samples, and an identical field appearance, one contains a population of five much younger detrital grains, suggesting a maximum deposition age of ∼1500 Ma. This is well outside the age-range of the Manshya River Group and might suggest correlation with the youngest sequence of the Muva Supergroup; the Mesoproterozoic Kasama Formation. This inference should, however be treated with extreme caution as dating of that formation itself rests on the age of a single detrital zircon. Highlights: Detrital zircons suggest maximum depositional age of Mafingi Group is ∼1800 Ma. Correlation with Manshya River Group (Muva Supergroup) confirmed. One younger sample (∼1500 Ma) might correlate with Kasama Formation of Zambia. No Irumide effects detected. High-grade Pan-African metamorphism recorded in one sample ("Virauli Quartzite").